First-year Students’ Best Online Learning Experiences: The Voices of Geography Students - Sibanda, Arorisoe; Manik, Sadhana (Papanda Publishier, 2025)
The experiences of students in first-year university modules continue to be an area of global interest. The grand narrative in higher education literature during the COVID-19 pandemic was students’ experiences with online learning challenges. This paper departs from this narrative to focus on students’ best online experiences at one public higher education institution in one of the poorest provinces in South Africa. The study was a mixed-method instrumental case study in a predominantly ‘face-to-face’ institution before the pandemic. Our theoretical architecture employed Connectivism (Siemens 2005) learning theory closely aligned with collaborative learning. We draw on the data from one campus, in a large class where 667 first-year students were asked to complete an online questionnaire (a high response rate of 35% was achieved). Students’ best online teaching and learning experiences included their supportive lecturers, enhanced interactions and engagement with the lecturer, easy access to teaching and learning materials uploaded to the ‘learn’ platform and access to technological advancements and training, which led to improved online skills. Given students’ best teaching and learning experiences, we recommend upscaling the study with a larger sample of first-year modules across multiple campuses of the institution. There is the potential to provide the impetus for fashioning a more nuanced hybrid teaching and learning environment for first-year students in the future. We recommend, for the future, a greater balance in the curriculum between multiple modes of instruction. Keywords: COVID-19, online learning, connectivism, students’ experiences